Optimization of Factors Affecting the Performance of a Fluidized Bed Dryer - Çelen, Soner; Pektaş, Sultan (2024)
This study investigated the theoretical, analytical, and experimental effects of parameters such as bed height, air velocity, and air temperature on drying using a fluidized bed dryer. The objective was to examine how these parameters influence the drying process of salt products in a pilot fluidized bed dryer and establish the foundation for the development of a future full-scale machine. Salt products with an initial moisture content of 3% were used in all experimental trials. The pressure drop was determined by calculating the minimum fluidization rate, Archimedes and Reynolds number. The calculated values were compared with the analyses conducted using the Multiphase Flow with Interphase eXchanges (MFIX) program and the tests performed on the pilot-scale static fluidized bed dryer equipment to verify the accuracy. Upon comparing the parameters in fluidized bed drying, it was concluded that the increase in air velocity had a more significant impact on the pressure drop than what was predicted in the theoretical calculations. Nevertheless, it was noted that the analysis was significantly impacted by the height of the bed.
Keywords: Salt